Analisis Capaian Program Merdeka Belajar Kampus Merdeka Prodi Pendidikan Luar Sekolah Universitas Negeri Semarang - Muarifuddin, Muarifuddin; Desmawati, Liliek; Sutarto, Joko; Fakhruddin, Fakhruddin; Suminar, Tri; Sudarmaji, Rosita Damayanti Berliana; Ciptaningtyas, Gentur; Hasdiani, Tanisa (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2024)
The Department of Nonformal Education, Faculty of Education, Universitas Negeri Semarang (PLS FIP UNNES) in 2022 is holding the MBKM program for Building Villages and Humanitarian Projects. The aim of the research is to analyze the learning outcomes of graduates, the learning achievements of recognition courses, the profiles of PLS FIP UNNES graduates through the MBKM program for Building Villages and Humanitarian Projects. The research design uses descriptive quantitative and qualitative descriptive approaches with survey respondents to 39 MBKM students for Building Villages and Humanitarian Projects. Data were also obtained from 11 research subjects including various BKKBN program managers. Analysis using descriptive statistics and qualitative descriptive. The research results show that graduate learning achievement (CPL), course learning achievement (CPMK) with an average of at level 4 of the maximum level 5 achievement. The relevance of the MBKM program is very high in growing graduate competency outcomes. The high profile of graduates is also closely related to the competence of the workforce needed by various BKKBN programs.Keyword: learning outcome; MBKM; nonformal education.